Immunological storm and multiple organ damage by COVID-19 - A. Yaser Arafath; S. Aifa Fathima; Anushara Prabhakaran; Saqib Hassan; Ragothaman Prathiviraj; George Seghal Kiran; Joseph Selvin (Medicine in Omics, 2024)
The official recording outbreak COVID-19 virus was in Dec 2019. When it affects humans, it affects almost all age groups, especially aged people. COVID-19 becomes a Global pandemic within a short period. The primary consequence of this infection is that it targets the individual's respiratory system and causes severe acute respiratory syndrome (SARS-CoV-2). Research efforts were made internationally to find a proper vaccine. Here, with the mechanism of action, this review provides the infection mechanism, Immunological changes, and associated organ damage.